Pentingnya Pembentukan Koperasi Bagi Petani Kopi di Desa Sumber Urip Kota Wlingi Blitar (Ibm Petani Kopi) - Loesita Sari; Yulita Pujiharti (IKIP Budi Utomo Malang, 2019)
The goal of the study was to give solution to people of Plumbangan village Sumber Urip Wlingi Blitar through Budi Luhur community so that their coffee beans could be more expensive than before. Therefore, through the study, people there were given and facilitated special tool and machine to change the coffee bean into powder. Besides, it also gave high awareness to people in the village to improve their income. Of the activities done by the team in Sumber Urip village, it was felt by the people there that Cooperation so called Sari Bumi Tani 6 was established managed by Mrs. Wagiyem which collaborated with the chief of LMDH. In addition, the team also distributed to donate coffee roasted machine and sheeler to facilitate people to do their activities. Based on the observation and monitoring to know the impact by forming Village Cooperation and giving the facility through coffee roasted machine and sheeler, the people could their activities well and their income could exceed.